Reactive oxygen species-responsive HET0016 prodrug-loaded liposomes attenuate neuroinflammation and improve neurological deficit in a rat model of juvenile traumatic brain injury - Qin, Jun; Chen, Xiaoli; Wang, Rui; Tian, Zedan; Li, Yang; Shu, Shiyu (Frontiers in Neuroscience, 2023)
The arachidonic acid pathway metabolite 20-hydroxyeicosatetraenoic acid (20-HETE) contributes to ischemia/reperfusion brain injury. Inhibition of 20-HETE formation can protect the developing brain from global ischemia. In previous studies, we have found that treatment with the 20-HETE synthesis inhibitor N-hydroxy-N-4-butyl-2-methylphenylformamidine (HET0016) can protect the immature brain from traumatic brain injury (TBI), but its hydrophobic nature limits its full potential. We designed a reactive oxygen species-responsive HET0016 prodrug, which consists of a thioketal link between HET0016 and stearyl alcohol (HET-TK-SA), and used the nanoprodrug strategy to successfully synthesize liposomes HET0016 prodrug liposomes (HPLs) to facilitate the application of HET0016 in protection from TBI. HPLs demonstrated spherical shape, size of about 127.8 nm, a zeta potential of −28.8 mv, a narrow particle size distribution and good stability. Male rats at postnatal day 16–17 underwent controlled cortical impact (CCI) followed by intravenous injection with vehicle or HET0016 (1 mg/kg, 2 h post-injury, once/day for 3 days). The results of the in vivo demonstrated that HPLs has good biosafety and can pass through the blood-brain barrier. Not only that compared with HET0016, HPLs better-inhibited inflammation and improved neuronal degeneration, which further led to lesion volume reduction, upgraded behavioral task performance, and ameliorated the degree of TBI impairment. Our results demonstrated HPLs could be a new strategy for juvenile TBI therapy.